Особенности эндодонтического лечения премоляров со сложной системой корневых каналов. Часть II (Эндодонтия Today, 2020)
One of the source of the bad quality endodontic treatment leading to the development of the chronical periapical lesions may be missed and unfilled root channel. Premolars are teeth with multiple root canal system. Authors show that inflammatory complications in premolars happen even often than in molars. In this review teeth (pemolars) investigation method helping in acessesory root canal detection is offered and cases of the endodontic treatment of the premolars with multiple root canals are described.